Pretreatment drug use characteristics and experiences among patients in a voluntary substance abuse treatment center in Malaysia: A mixed-methods approach. Issue 4 (1st October 2016) - Krishnan, Archana; Brown, Shan-Estelle; Ghani, Mansur A.; Khan, Farrah; Kamarulzaman, Adeeba; Altice, Frederick L.
ABSTRACT: Background: Drug use in Malaysia remains a significant public health and social problem despite implementation of harsh punitive drug policies such as forcibly placing suspected drug users into compulsory drug detention centers (CDDCs). Following criticism over human right violations in CDDCs, Malaysia has begun to transition towards voluntary drug treatment centers known as Cure & Care (C&C) centers. To best serve the needs of regional C&C centers, data on drug use are essential among patients accessing treatment. Using a mixed-methods approach, the authors examined pretreatment drug use characteristics and experiences with addiction treatment among C&C patients in Kelantan—a religiously conservative state in northeast Malaysia with high prevalence of drug use but where limited data are available on drug use patterns. Methods: A mixed-methods study utilizing surveys ( n = 96) and semistructured interviews ( n = 20) was conducted among a convenience sample of inpatients and outpatients at the Pengkalan Chepa C&C Center in Kelantan. Results: Survey results showed that 89.6% of participants met screening criteria for moderate to severe addiction severity. Nearly 90% reported lifetime illicit amphetamine (syabu, meth, ice, and pil kuda) use, followed by alcohol (60.4%) and opioids (52.1%). Qualitative results pointed to the powerful influence of peer networks in drug initiation and relapse, and the positive effect of the C&C center on drug rehabilitation. Conclusions: The drug use profile of the Kelantan C&C center enrollees shows extensive pretreatment amphetamine use, polysubstance use, and injection drug use, including high-risk behaviors such as sharing needles, syringes, and containers. Evidence points to the need for integration of social support–oriented practices and behavioral interventions into the rehabilitation of drug users in this region.